Heat shock protein 70 promotes cell survival by inhibiting lysosomal membrane permeabilization. - Nylandsted, J; Gyrd-Hansen, M; Danielewicz, A; Fehrenbacher, N; Lademann, U; Høyer-Hansen, M; Weber, E; Multhoff, G; Rohde, M; Jäättelä, M (2004)
Heat shock protein 70 (Hsp70) is a potent survival protein whose depletion triggers massive caspase-independent tumor cell death. Here, we show that Hsp70 exerts its prosurvival function by inhibiting lysosomal membrane permeabilization. The cell death induced by Hsp70 depletion was preceded by the release of lysosomal enzymes into the cytosol and inhibited by pharmacological inhibitors of lysosomal cysteine proteases. Accordingly, the Hsp70-mediated protection against various death stimuli in Hsp70-expressing human tumor cells as well as in immortalized Hsp70 transgenic murine fibroblasts occurred at the level of the lysosomal permeabilization. On the contrary, Hsp70 failed to inhibit the cytochrome c-induced, apoptosome-dependent caspase activation in vitro and Fas ligand-induced, caspase-dependent apoptosis in immortalized fibroblasts. Immunoelectron microscopy revealed that endosomal and lysosomal membranes of tumor cells contained Hsp70. Permeabilization of purified endo/lysosomes by digitonin failed to release Hsp70, suggesting that it is physically associated with the membranes. Finally, Hsp70 positive lysosomes displayed increased size and resistance against chemical and physical membrane destabilization. These data identify Hsp70 as the first survival protein that functions by inhibiting the death-associated permeabilization of lysosomes.